Tapia syndrome following anterior cervical surgery in a patient with diffuse idiopathic skeletal hyperostosis: a case report - Yan, Liuxin; Gao, Hongyang; Zhen, Zihao; Yu, Zhiming (Frontiers in Surgery, 2026)
BackgroundTapia syndrome is a rare complication characterized by concurrent injury to the hypoglossal and vagus nerves, most often associated with airway manipulation during general anesthesia. Patients with diffuse idiopathic skeletal hyperostosis (DISH) present unique anatomical challenges for anterior cervical surgery, increasing the risk of airway-related nerve injury.Case presentationWe report the case of a 73-year-old man with cervical DISH and myelopathy who underwent anterior cervical corpectomy and fusion (ACCF). Despite an uneventful intraoperative course, the patient developed postoperative hoarseness and delayed airway obstruction due to posterior tongue collapse. Laryngoscopy ruled out vocal cord injury. A diagnosis of Tapia syndrome was made based on the combination of hypoglossal and vagus nerve palsy. The patient required temporary tracheostomy and received glucocorticoid therapy, neurotrophic agents, and rehabilitation. All symptoms gradually resolved, and the patient was discharged after 40 days with near-complete recovery.ConclusionThis case emphasizes the need for careful airway management and early recognition of cranial nerve dysfunction in patients with DISH undergoing anterior cervical surgery. Individualized preoperative anatomical assessment, meticulous intraoperative airway control, and vigilant postoperative monitoring are essential to reduce the risk of this rare but significant complication.